Successfully cured a rare case of esophageal squamous cell carcinoma combined with hepato-gastric schwannoma using robot-assisted surgery: case report - Zhang, Qun-Xian; Guo, Qiang; Liu, Hua; Zhou, Jun; Guo, Jia-Long; Zhang, Jun (Frontiers in Oncology, 2025)
Esophageal squamous cell carcinoma (ESCC) is among the most common malignant tumors. Robot-assisted surgery using the cervical and thoracoabdominal incisions is a viable treatment option for ESCC. This case report presents a rare instance of ESCC complicated by hepato-gastric schwannoma, offering clinical insights and treatment strategies. A 69-year-old patient diagnosed with ESCC via gastroscopy was admitted without complaints of dysphagia. Gastroscopy revealed swollen erosions approximately 32–38 cm from the incisors. Pathology confirmed high-grade intraepithelial neoplasia and squamous cell carcinoma (SCC) of the esophageal squamous epithelium. Endoscopic ultrasonography revealed a lesion with moderate to low echogenicity, indicating local involvement of the muscularis propria. An enhanced upper abdominal computed tomography (CT) scan showed a 3.3 × 2.6 cm mass in the hepatogastric space, accompanied by mildly enlarged lymph nodes—the largest measuring 0.8 cm—which suggested possible metastasis. After a comprehensive evaluation, the patient underwent robot-assisted thoracoscopic partial esophagectomy, intrathoracic esophagogastric anastomosis, thoracoscopic adhesiolysis, and mediastinal lymphadenectomy under general anesthesia. Postoperative pathology showed a poorly to moderately differentiated ESCC (pT1aN0M0) measuring 3 cm × 2.7 cm × 0.2 cm, invading the lamina propria without vascular or neural invasion, and there is a schwannoma with a diameter of 3.5cm. No cancer was found at the gastric margin or anastomotic stump. Lymph nodes—including right and left recurrent laryngeal, subcarinal, left gastric, paracardiac, upper paraesophageal, and hepatogastric—were free of metastasis. The patient received postoperative supportive care, including antibiotics, acid suppression, mucolytics, antispasmodics, intravenous nutrition, and albumin supplementation. On postoperative day 7, iodine water angiography revealed no significant abnormalities at the anastomosis, permitting the reintroduction of a liquid diet. The patient was discharged in stable condition on postoperative day 10. No evidence of progression or recurrence has been observed during the follow-up. This report aims to inform clinical practice with insights into the management of rare coexisting pathologies